Rankine source time domain method for nonlinear ship motions in steep oblique waves. (3rd April 2019) - Riesner, Malte; Chillcce, Guillermo; el Moctar, Ould
ABSTRACT: This article presents a weakly nonlinear time domain Rankine source boundary element method to calculate wave-induced ship motions. Radiation forces were calculated using convolution integrals, whereas Froude–Krylov and hydrostatic forces were obtained from ship positions relative to the instantaneously wetted surface. The nonlinear rigid body motion equations were coupled with the flow equations to enable reliable predictions also in finite amplitude (steep) waves. A system of soft springs prevented excessive low-frequency motions of the ship, but allowed it to move in six degrees of freedom. Numerical results of a 14, 000TEU container ship at two different forward speeds in oblique waves of different steepness were validated against comparable ship motions obtained from available experimental towing tank measurements and a frequency domain method. The influence of wave steepness and wave heading on ship motions was of particular interest.